The Influence of Leadership Style and Organizational Commitment on Work Motivation and Organizational Performance (Case Study on the National Creative Economy Movement DPC (GEKRAFS) Probolinggo Regency) - Achmad Basofitrah; Hadi Sunaryo; Supriyanto Supriyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of leadership style and organizational commitment on work motivation and organizational performance. The population of this study are members of the National Creative Economy Movement DPC (GEKRAFS) Probolinggo Regency. In this study, the sampling technique used the entire population so that the respondents were determined to be 40 respondents. The data analysis method is descriptive quantitative. Quantitative analysis was performed using SmartPLS. In this study, the results showed that leadership style and organizational commitment had a significant effect on organizational performance, leadership style and organizational commitment had an effect on motivation, while motivation had no effect on organizational performance.